Rethinking the relevance of microplastics as vector for anthropogenic contaminants: adsorption of toxicants to microplastics during exposure in a highly polluted stream - analytical quantification and assessment of toxic effects in zebrafish (Danio rerio) - Hanslik, Lisa; Huppertsberg, Sven; Kämmer, Nadine; Knepper, Thomas P.; Braunbeck, Thomas (The science of the total environment, 2022)
Given the increasing amounts of plastic debris entering marine and freshwater ecosystems, there is a growing demand for environmentally relevant exposure scenarios to improve the risk assessment of microplastic particles (MPs) in aquatic environments. So far, data on adverse effects in aquatic organisms induced by naturally exposed MPs are scarce and controversially discussed. As a consequence, we investigated the potential role of MPs regarding the sorption and transfer of environmental contaminants under natural conditions. For this end, a mixture of four common polymer types (polyethylene, polypropylene, polystyrene, polyvinyl chloride) was exposed to natural surface water in a polluted stream for three weeks. Samples of water, MP mixture, sediment, and suspended matter were target-screened for the presence of pollutants using GC/LC-MS, resulting in up to 94 different compounds. Possible adverse effects were investigated using several biomarkers in early developmental stages of zebrafish (Danio rerio). Exposure to natural stream water samples significantly inhibited acetylcholinesterase activity, altered CYP450 induction and modified behavioral patterns of zebrafish. In contrast, effects by samples of both non-exposed MPs and exposed MPs in zebrafish were less prominent than effects by water samples. In fact, the analytical target screening documented only few compounds sorbed to natural particles and MPs. Regarding acute toxic effects, no clear differentiation between different MPs and natural particles could be made, suggesting that - upon exposure in natural water bodies - MPs seem to approximate the sorption behavior of natural particles, presumably to a large extent due to biofilm formation. Thus, if compared to natural inorganic particles, MPs most likely do not transfer elevated amounts of environmental pollutants to biota and, therefore, do not pose a specific additional threat to aquatic organisms.